(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
In the contemporary world, where information technology finds application in all spheres of life, the issue of the effectiveness of teaching a foreign language to future engineers emerges as a particularly significant one. It has been noted that traditional teaching methods tend to demonstrate a lack of sufficient effectiveness in the development of lexical competence in future specialists, thus giving rise to a significant need for the exploration of innovative, new approaches to be developed. One such approach that has been identified is gamification, which involves the integration of game elements into the learning process. The purpose of the research is to analyse the peculiarities of using gamified learning technology in the formation of future engineers’ lexical competence and to develop practical recommendations for its implementation of game methods in the process of studying the discipline “Foreign Language (English) for Specific Purposes”. The study used a complex of methods, in which theoretical analysis of scientific literature on gamification and lexical competence development, student interviews, pedagogical monitoring of the learning process and an experimental study of the effectiveness of gamified learning materials were used. As a result, the theoretical basis for the use of gamification methods in the formation of future specialists’ lexical competence has been determined. It has been found that gamification helps to increase students’ motivation to learn, activate their cognitive activity, develop independence and responsibility. The article provides specific examples of game-based teaching methods for the formation of lexical competence, which includes the following components: game goal, competition elements, virtual reality, and interactive tasks. The study results have confirmed the effectiveness of the developed methodology in the educational process. It has been found that students who studied using gamified learning materials demonstrate a significantly higher level of lexical competence than those who studied using traditional methods. As a conclusion, the authors emphasise that gamification contributes to the development of an interesting and motivating learning environment, which positively affects the acquisition of lexical material.